GENOTYPING OF VIRULENCE FACTORS OF ESCHERICHIA COLI (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The most common bacteria that can cause UTIs is Escherichia coli. One of the most common types of infectious disorders in humans is urinary tract infections (UTIs). The bacteria Escherichia coli typically causes pyelonephritis and cystitis and is considered a dominant bacterium. The purpose of this study was to identify the presence of certain virulence genes, such as those encoding fimbriae, hemolysin synthesis, and aerobactin, in one hundred Escherichia coli isolates collected from patients presenting with UTI symptoms in both the lab and the clinic at Al zahraa hospital in Wasit province. Among the virulence factors examined, fimH was the most prevalent. There was a 73% prevalence of the fimbriae type 1 (fimH) gene, a 46% prevalence of pyelonephritis associated pili (pap) gene, a 32% prevalence of S-family adhesions (sfa) gene, and a 47% prevalence of hemolysin (hly) gene.